Novel Selenium-Mediated Rearrangements and Cyclisations - Shahzad, Sohail Anjum (Springer Theses, Recognizing Outstanding Ph.D. Research, 2013)
In his thesis, Sohail Shahzad carefully investigates carbon nucleophiles in selenocyclisations, as well as reaction protocols for performing such reactions catalytically. After a comprehensive introduction to the element selenium, the author goes on to report the synthesis of several substrates for carbocyclisation reactions and the use of selenium reagents for the preparation of dihydronaphthalenes. Further chapters detail electrophilic selenium-mediated reactions, and novel strategies using selenium catalysts together with stoichiometric amounts of hypervalent iodine reagents as oxidants to convert stilbene carbosylic acids into the corresponding isocoumarins. This thesis outlines some excellent new synthetic routes which will be useful tools for synthetic organic chemistry in the future.